Mini review on environmental issues concerning conventional gas hydrate inhibitors - Haq, I.U. (John Wiley and Sons Inc, 2021)
In the offshore oil and gas fields, the formation of gas hydrates creates critical issues, and these issues or challenges become more pervasive as productive activities proceed to deep sea waters. Further, a number of chemical additives that are used to prevent gas hydrate formation in pipelines pose toxicity issues and are harmful to the environment. Commercially available inhibitors such as methanol, glycols, polyvinyl caproclatum (PVCap), and polyvinylpyrrolidone (PVP), which are being used for gas hydrate mitigation, have shown toxicity issues such as corrosion and mass loss due to their volatile nature, resulting in their high consumption. Methanol and glycols are identified as thermodynamic hydrate inhibitors (THIs), while PVCap and PVP are classified as low-dosage hydrate inhibitiors. There has been considerable discussion in the literature on whether to use THIs or low-dosage gas hydrate inhibitors (LDHIs) but less discussion on their toxicity and harmful effects on the environment. Therefore, in this mini review we intend to throw light on the environmental issues concerning conventional gas hydrate inhibitors used currently. Â© 2021 American Institute of Chemical Engineers